PELAKSANAAN PENDIDIKAN AGAMA ISLAM SECARA FORMAL PADA MASYARAKAT NELAYAN TERPENCIL TANAH KUNING - Abdul Arif (Universitas Muhammadiyah Prof Dr Hamka, 2019)
The concept of fostering fishing communities within the framework of a sustainable fisheries development perspective in Indonesia needs to be studied properly, precisely and touches on the targets to be achieved. This study aims to 1) Determine the character of the remote community of Tanah Kuning fishermen, 2) Systems and practices of the implementation of Islamic education, 3) Supporting and inhibiting factors in Islamic education, 4) Educational models that are appropriate to the characteristics of the remote fishing communities of Tanah Kuning. The results of this study include people with livelihoods as fishermen who are not willing to make changes unless someone starts, the education system has not been able to run in accordance with the existing objectives. The supporting and inhibiting factors produced were religious teachers who still received respect from the community and adequate school buildings, monotonous teachers, inadequate books, only one teacher, and community perceptions that considered education less important. The educational model used the Gagne model which creates external conditions in line with the internal conditions of student learning processes.